2016
DOI: 10.1080/09540261.2016.1217829
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence, HIV, and mental health: a triple epidemic of global proportions

Abstract: Intimate partner violence (IPV) is a global health problem of epidemic proportions, affecting a third of women across the globe and as many as 60% in heavily affected regions of Africa. There is strong evidence that risk of IPV is heightened in HIV-infected women, and emerging evidence linking experiencing IPV and/or HIV to a higher likelihood of experiencing mental health problems. This triple burden makes women in Africa, living in the epicentre of HIV, all the more vulnerable. In this synthesis, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 63 publications
5
60
0
Order By: Relevance
“…At the relationship level, AIW identified IPV, and inability to negotiate condom use, as factors that placed women at risk for HIV infection. The relationship between IPV and HIV is supported by many studies (e.g., Li et al, 2014; Mitchell, Wight, Van Heerden, & Rochat, 2016). In a systematic review and meta-analysis of 28 studies (Li et al, 2014) involving 16 countries, physical IPV, and both physical and sexual IPV were significantly associated with HIV infection (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…At the relationship level, AIW identified IPV, and inability to negotiate condom use, as factors that placed women at risk for HIV infection. The relationship between IPV and HIV is supported by many studies (e.g., Li et al, 2014; Mitchell, Wight, Van Heerden, & Rochat, 2016). In a systematic review and meta-analysis of 28 studies (Li et al, 2014) involving 16 countries, physical IPV, and both physical and sexual IPV were significantly associated with HIV infection (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…This concept refers to an abuse within an intimate relationship that can be psychical, sexual or psychological 34 . Studies from high-income countries, such as the United States, have found an alarming rate of IPV in the LGBT population 35,36 .…”
Section: Key Topics In Hiv Prevention For Lb Womenmentioning
confidence: 99%
“…Authors such as Miller et al 35 have suggested that the obstacles that have hindered the recognition of IPV in LB women are ingrained in gender norms because programs and policies have been created by focusing on heterosexual women and they have neglected the people outside that category. Thus, poor law enforcement towards same-sex IVP; poor social support; stigma within the judicial system and health care centers; and social and individual perceptions of less severity towards same-sex IVP, have contributed to the low attention and underreporting of this issue 34 . It is important to mention that, although the association between IVP and HIV exposure has been described in heterosexual women and gay men, because it reduces condom negotiation 34,38 , the link is still understudied in LB women, but it is important to address it in prevention programs due to the mentioned rates.…”
Section: Key Topics In Hiv Prevention For Lb Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Also included are reviews focusing on under-served populations' experiences of abuse. Mitchell, Wight, Van Heerden, & Rochat (2016) draw attention to the 'triple epidemic' of HIV infection, intimate partner violence, and mental health problems in Africa, estimating that these three burdens may affect up to 30% of African women concurrently. Khalifeh, Oram, Osborn, and Johnson (2016) highlight the vulnerability of women with severe mental illness to domestic violence: their systematic review finds that between 15-22% report recent domestic violence.…”
Section: Editorialmentioning
confidence: 99%